Evolution of centrifugal distillation system with a thermoelectric heat pump for space missions: Part 1. Review of publications on centrifugal distillation in the period of 1990 – 2017 - Rifert, V.G.; Anatychuk, L.I.; Barabash, P.O.; Usenko, V.I.; Strykun, A.P.; Solomakha, A.S.; Petrenko, V.G.; Prybyla, A.V. (Journal of Thermoelectricity, 2019)
The article describes the main results of the development and testing of a multistage centrifugal vacuum distillation (MCVD) system with a thermoelectric heat pump (THP). For the most part, these works present information on the integral characteristics of the system, namely: distillate capacity, specific energy consumption per unit mass of the obtained distillate and distillate quality during evaporation (concentration) of an aqueous solution of NaCl, urine and mixtures of urine with condensate and urine with condensate and hygienic water. Bibl. 29, Tabl. 5.